Dampak Pembangunan Infrastruktur dalam Mendorong Pertumbuhan untuk Mengurangi Tingkat Kemiskinan di Indonesia Tahun 2013 – 2017: Institut Pertanian Bogor - Edi victara Tinambunan; Muhammad Findi; Yeti Lis Purnamadewi (IPB University, 2019)
Poverty is a social problem that has not been resolved until now. One way to overcome poverty is through equitable and targeted infrastructure development throughout Indonesia. This study analyzes the effect of infrastructure development on poverty through economic growth in Java and outside Java. The analytical tools in this study are simultaneous panel and typology klassen equipped with two structural equations. This study found that electricity, education, transportation and water infrastructure affect economic growth in Java. Meanwhile education, electricity, health and transportation infrastructure affect economic growth outside Java. Population and economic growth both affect poverty in Java and outside Java.